The role of nature reserves in sustainable ecotourism Imam Saud bin Abdul-Aziz Reserve (Mahazat Al-Sayd) - Alkuhaily, Samah Rabah (Journal of Humanities & Social Sciences, 2024)
The study showed that nature reserves play a vital role in promoting ecotourism and sustainable development. Which contributes to attracting tourists, developing their awareness and awareness of the important environmental aspects that require their preservation, which promotes sustainable tourism in the region .  Natural reserves have their own aesthetic character, such as Mahazat Al-Sayd Reserve located in the western region of Saudi Arabia, (180) kilometers northeast of the city of Taif and belonging to the Makkah region. The reserve has contributed significantly to the preservation of many vital aspects. The study shed light on the nature reserves in the Makkah region and their effective role in the aspect of ecotourism and sustainable development, which benefits various environmental, social and economic aspects of the region. The study aimed to identify the role of nature reserves in sustainable ecotourism . The study followed the descriptive and analytical approach by introducing the study area based on theoretical studies. Analysis through satellite visualizations from the LANDSAT8 satellite. The study found that the reserve is one of the pristine areas in which there is no existing ecotourism in the region, but there are plans to establish this type of tourism in the future through workshops held for workers at the site. The study recommended that there should be no ecotourism in the area because it is a natural area and animals were not present except because the reserve is far from human activity. This type of sensitive environment may suit ecotourism, which depends on walking, enjoying, communicating with nature and getting to know birds and animals in the reserve.
Keywords: Nature reserves; Ecotourism; Sustainable Development; Sustainable Tourism